Complementary Feeding: Review of Recommendations, Feeding Practices, and Adequacy of Homemade Complementary Food Preparations in Developing Countries – Lessons from Ethiopia - Abeshu, Motuma Adimasu; Lelisa, Azeb; Geleta, Bekesho (Frontiers in Nutrition, 2016)
Breastfeeding provides the ideal food during the first 6 months of life. Complementary feeding is the process starting when breast milk alone is no longer sufficient, the target age being between 6 to 23 months. The gap between nutritional requirement and amount obtained from breast milk increases with age. For energy, 200kcal, 300kcal and 550kcal per day is expected to be covered by complementary foods at 6-8, 9-11 and 12-23 months, respectively. In addition, the complementary foods must provide relatively large proportions of micronutrients such as: iron, zinc, phosphorus, magnesium, calcium and vitamin B6. In several parts of the developing world, complementary feeding continues as a challenge to good nutrition in children. In Ethiopia, only 4.2% of breastfed children of 6–23 months of age have a minimum acceptable diet. The gaps are mostly attributed to either poor dietary quality or poor feeding practices, if not both. Commercial fortified foods are often beyond the reach of the poor. Thus, homemade complementary foods remain commonly used. However, unfortified complementary foods that are predominantly plant-based provide insufficient amounts of key nutrients (particularly iron, zinc and calcium) during the age of 6 – 23 months even, when based on an improved recipe. This review thus assessed complementary feeding practice and recommendation and reviewed the level of adequacy of homemade complementary foods.